Hubungan Umur Pemberian Pertama Makanan Pendamping ASI (MP-ASI) dengan Status Gizi Anak 7-36 bulan - Kalsum, Ummi (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2015)
ABSTRACT One of health problem in Indonesia is malnutrition in under five children. Malnutrition appeared in rural areas caused by poverty, nutrition knowledge, complementary feeding and environmental sanitation. We studied whether the first ages of introduction complementary food (MP-ASI) is associated with nutritional status in 7-36 mo of children. It was a Case Control study. Data used came from Hearth/Positive Deviance Study Monitoring and Evaluation research conducted by SEAMEO TROPMED RCCN-UI. Children malnutrition (n=192) as research subject. Children with severe malnutrition (< -3 SD) as case group compared to moderate malnutrition (<-2 SD until -3 SD) with 1:1 comparison. Nutritional status counted by WAZ (WHO-NCHS). Main independent variable was first age of MP-ASI with covariate were children characteristics (age, sex, diarrhea, energy consumption, immediate breastfeeding); mother’s characteristics (education, knowledge, personal hygiene, and active feeding behavior) and family’s characteristics (number of children, family member, housing and sanitation facilities). The data analysis is done by chi-square and multivariate logistic regression. Results : the analysis shown significant association between first ages of MP-ASI (OR=0,187; 95% CI :0,052-0,673), personal hygiene (OR=2,053; 95% CI : 1,109-3,800) and number of underfive children (OR=2,067; 95% CI : 1,060-4,029) toward nutritional status. The study found protective effect to children with first age of MP-ASI < 6 mo compared to >= 6 mo although controlled by housing, diarrhea, mother’s education, family member, personal hygiene, immediate breastfeeding and number of underfive children (P=0,003). The first ages of introducing complementary food < 6 mo was protective effect to savere malnutrition in under five children compare to >= 6 mo, especially in low social economic status. Key Words : Feeding, breastfeed, nutritional status, malnutrition, underweight, underfive